BA6 Induces Apoptosis via Stimulation of Reactive Oxygen Species and Inhibition of Oxidative Phosphorylation in Human Lung Cancer Cells. (7th May 2019) - Cheng, Meng-Hsuan; Huang, Hung-Ling; Lin, Yen-You; Tsui, Kuan-Hao; Chen, Pei-Chin; Cheng, Shu-Yu; Chong, Inn-Wen; Sung, Ping-Jyun; Tai, Ming-Hong; Wen, Zhi-Hong; Chen, Nan-Fu; Kuo, Hsiao-Mei
Abstract : Lung cancer is the leading cause of cancer deaths in the world, with a five-year survival rate of less than 30%. Clinically effective chemotherapeutic treatments at the initial stage may eventually face the dilemma of no drug being effective due to drug resistance; therefore, finding new effective drugs for lung cancer treatment is a necessary and important issue. Compounds capable of further increasing the oxidative stress of cancer cells are considered to have anticancer potential because they possessed the ability to induce apoptosis. This study mainly investigated the effects of BA6 (heteronemin), the marine sponge sesterterpene, on lung cancer cell apoptosis, via modulation of mitochondrial reactive oxygen species (mtROS) and oxidative phosphorylation (OXPHOS). BA6 has cellular cytotoxic activities against a variety of cancer cell lines, but it has no effect on nontumor cells. The BA6-treated lung cancer cells show a significant increase in both cellular ROS and mtROS, which in turn caused the loss of mitochondrial membrane potential (MMP). The increase of oxidative stress in lung cancer cells treated with BA6 was accompanied by a decrease in the expression of antioxidant enzymes Cu/Zn SOD, MnSOD, and catalase. In addition, OXPHOS performed in the mitochondria and glycolysis in the cytoplasm were inhibited, which subsequently reduced downstream ATP production. Pretreatment with mitochondria-targeted antioxidant MitoTEMPO reduced BA6-induced apoptosis through the mitochondria-dependent apoptotic pathway, which was accompanied by increased cell viability, decreased mtROS, enhanced MMP, and suppressed expression of cleaved caspase-3 and caspase-9 proteins. In conclusion, the results of this study clarify the mechanism of BA6-induced apoptosis in lung cancer cells via the mitochondrial apoptotic pathway, suggesting that it is a potentially innovative alternative to the treatment of human lung cancer.